2023
DOI: 10.1007/s12672-023-00774-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy following immune checkpoint inhibitors in recurrent or metastatic head and neck squamous cell carcinoma: clinical effectiveness and influence of inflammatory and nutritional factors

Akihiro Sakai,
Koji Ebisumoto,
Hiroaki Iijima
et al.

Abstract: Objective This study aimed to evaluate the clinical effectiveness of chemotherapy following immune checkpoint inhibitors (ICI). The association between inflammatory and nutritional factors and prognosis has also been investigated. Methods We retrospectively reviewed the medical records of recurrent or metastatic head and neck squamous cell carcinoma (RMHNSCC) patients who received chemotherapy following ICI therapy. The response rate and survival a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Other clinical studies have suggested the compatibility of ICI with taxane anticancer agents in treating various cancers, including head and neck cancer [20, 21], melanoma [22], and NSCLC [23]. In a retrospective study by Sakai et al [20], chemotherapy following ICI treatment was highly effective in patients with head and neck cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other clinical studies have suggested the compatibility of ICI with taxane anticancer agents in treating various cancers, including head and neck cancer [20, 21], melanoma [22], and NSCLC [23]. In a retrospective study by Sakai et al [20], chemotherapy following ICI treatment was highly effective in patients with head and neck cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Other clinical studies have suggested the compatibility of ICI with taxane anticancer agents in treating various cancers, including head and neck cancer [20, 21], melanoma [22], and NSCLC [23]. In a retrospective study by Sakai et al [20], chemotherapy following ICI treatment was highly effective in patients with head and neck cancer. Most patients in this study (over 80%) received a paclitaxel based regimen, achieving a higher ORR compared to the TS-1 regimen.…”
Section: Discussionmentioning
confidence: 99%
“…It is still unclear whether the combination effects of PD-1/PD-L1 inhibitors and chemotherapies are synergistic or additive. Several retrospective studies have shown that exposure to immune checkpoint inhibitors improves the response to salvage chemotherapy in HNSCC, suggesting that immune checkpoint inhibitors may increase tumor sensitivity to chemotherapy [20,107].…”
Section: The Interaction Of Immune Therapy and Chemotherapymentioning
confidence: 99%
“…Further, the predictive value of PLR has been investigated in glioblastoma, where a relationship between PLR and overall survival in treatment-naïve patients was reported [6]. Finally, other cancers in which the role and potential utility of PLR are being currently investigated include head and neck squamous cell carcinoma [7], uroepithelial carcinoma [8], gastric cancer [9], and ovarian cancer [10].…”
Section: Introductionmentioning
confidence: 99%